Answer:
6, 9 & 12
Step-by-step explanation:
let x represent the age of the youngest kid
if the oldest kid is twice the age of the youngest, then it would be 2x
if the middle kid is 3 years older than the youngest, let this be x+3
if their ages in total is 27, then the equation is
x+2x+x+3=27
combine like terms first
4x+3=27
subtract 3 from both sides
4x=24
divide both sides by 4
you get 6. The youngest kid is 6.
For the oldest kid, the equation is 2x=2 times 6=12
the age of the middle child, equation is (x+3)=6+3=9
Hoped this helped!